2014
DOI: 10.4137/oed.s14019
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Surgical Removal of the Eye in Rural Areas in Cameroon

Abstract: OBJECTIVETo determine the main clinical indications for surgical removal of the eye in rural areas in Cameroon.DESIGNRetrospective non-comparative case series.PARTICIPANTSA total of 253 patients presenting to the Manna eye clinic Nkongsamba who underwent destructive eye surgery (DES) between January 2006 and December 2010 were reviewed.MAIN OUTCOME MEASUREAge, gender, occupation, prior medication, visual acuity, operation indications, and type of operation.RESULTSThere were 58.10% (n = 147) men and 41.90% (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
(19 reference statements)
1
5
2
Order By: Relevance
“…Our study showed that infection/inflammation accounted for 17% of cases, which was lower compared with the incidence in developing countries, such as Cameroon 23 (51%) and Saudi Arabia 27 (46%). Women were more often affected by infection/inflammation, such as keratitis and endophthalmitis, and this is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Our study showed that infection/inflammation accounted for 17% of cases, which was lower compared with the incidence in developing countries, such as Cameroon 23 (51%) and Saudi Arabia 27 (46%). Women were more often affected by infection/inflammation, such as keratitis and endophthalmitis, and this is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 52%
“…Reports on enucleation patterns have come from the United States, 3,[7][8][9] Europe, [10][11][12][13][14] Asia, [15][16][17][18][19] Africa, [20][21][22][23][24] and the Middle East. [25][26][27] The clinical indications for and causes Crown Copyright & 2017 Published by Elsevier Inc on behalf of the Canadian Ophthalmological Society.…”
mentioning
confidence: 99%
“…Indeed, contrary to the goal of cataract surgery, which aims to improve vision; the main goal of mutilating surgery is to improve the patient's quality of life [7]. The etiologies of this surgery in our study were dominated by infectious pathologies (58.61%) and tumoral affections (29.30%) Our findings were superimposable with those of Kagmeni [8], Pandey [2], Nwosu [1]. These results differed from those of Diomandé [9] and Meda [10], who observed a predominance of traumatic pathologies in their series.…”
Section: Discussioncontrasting
confidence: 42%
“…In the literature, the reported mean age was 29-53 years, and it was observed that in developing countries, eye removal surgeries occur at younger ages, whereas in developed countries they occur in older ages. 2 , 3 , 5 , 6 , 9 In our study, the most frequent indication in evisceration surgeries was trauma, whereas it was malignancy in enucleation surgeries, which explains the younger age of evisceration patients, and the older age of enucleation patients.…”
Section: Discussionmentioning
confidence: 59%
“… 19 Infectious reasons make the most common eye removal indications in countries or regions of low socioeconomic conditions. 8 , 9 The developments in the diagnosis and treatment of endophthalmitis in recent years, the existence of effective antimicrobials and their intravitreal applications enable medical therapy for endophthalmitis. 5 In our study, no eye removal surgery was performed after 2005 for the indication of endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%